Measuring the volume of the digital economy and the effectiveness of digitalisation - Goloventchik, Galina G.; Yanhai, He (Journal of the Belarusian State University. Economics, 2022)
The article analyses and summarises approaches to measuring the contribution of the digital economy to gross domestic product and economic growth. The methods of calculating the effects of digitalisation are applicable not only to the national economy, but also to individual sectors and branches of the economy.
Keywords: digital economy; digitalisation; system of national accounts; gross domestic product; economic growth